Formulasi Sediaan Sabun Padat Herbal Dari Serbuk Kulit Buah Pisang Ambon (Musa paradisiaca var. sapientum L.) - Muthmainna B (Journal Syifa Sciences and Clinical Research, 2022)
Most of the soaps in the market are chemical soaps. Chemical soap is a soap that uses Sodium Laurat Sulposphat (SLS) as its main raw material. Ambon banana is a type of banana that is widely consumed by the people of Indonesia. Ambon banana (Musa paradisiaca var. sapientum (L.) Kunt.) are also known to contain saponin, glycoside, tannin, alkaloid, and flavonoid. Ambon banana peel has a higher antioxidant activity than the pulp. The purpose of this study was to evaluate the formula of herbal solid soap from Ambon banan peel powder. This type of research is experimental using a simple formula design. The activity stage includes sample processing, product manufacture, and product quality analysis testing. The test includes an organoleptic test where the results of the data obtained are brown yellow solid soap, greentea lily scent, smooth texture, and rectangular shape, the pH test has an alkaline pH of 9, foam height test has a foam height of 125 mm, 15% water content test, and irritation test that does not cause irritation to the skin of the panliests. From the results of the research that has been done, it can be concluded that the soap formula used meets the requirements of the SNI standard which is safe and good for use on human skin.